2021
DOI: 10.3390/min11080833
|View full text |Cite
|
Sign up to set email alerts
|

Visual Imaging of Benthic Carbonate-Mixed Factories in the Ross Sea Region Marine Protected Area, Antarctica

Abstract: Marine biogenic skeletal production is the prevalent source of Ca-carbonate in today’s Antarctic seas. Most information, however, derives from the post-mortem legacy of calcifying organisms. Prior imagery and evaluation of Antarctic habitats hosting calcifying benthic organisms are poorly present in the literature, therefore, a Remotely Operated Vehicle survey was carried out in the Ross Sea region Marine Protected Area during the 2013–2014 austral summer. Two video surveys of the seafloor were conducted along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…CCA are even more tolerant of low-light conditions due to their low photosynthetic capacity (Littler et al, 1985;Roberts et al, 2002;Nelson, 2009). CCA are found within most coastal habitats (Littler et al, 1985), including (Zaneveld and Sanford, 1965;Schwarz et al, 2005;Castellan et al, 2021), and are observed at depths greater than any other local marine algae species (McConnaughey and Whelan, 1997). This may explain the exclusion of bathymetry from the CCA LightGBM model.…”
Section: Discussionmentioning
confidence: 99%
“…CCA are even more tolerant of low-light conditions due to their low photosynthetic capacity (Littler et al, 1985;Roberts et al, 2002;Nelson, 2009). CCA are found within most coastal habitats (Littler et al, 1985), including (Zaneveld and Sanford, 1965;Schwarz et al, 2005;Castellan et al, 2021), and are observed at depths greater than any other local marine algae species (McConnaughey and Whelan, 1997). This may explain the exclusion of bathymetry from the CCA LightGBM model.…”
Section: Discussionmentioning
confidence: 99%
“…Given the presence of sea ice (particularly fast ice) for most of the year, understanding of the coastal biogeography and ecosystem processes is limited to a restricted number of areas at depths accessible by dive-based operations (Cummings et al 2018). Such constraints are being overcome by the use of remote visual techniques, which are emerging as low-impact tools for collecting visual information on sh and benthic communities (Castellan et al 2021). In recent years, visual methodologies have been applied worldwide to improve current knowledge on the spatial patterns of biodiversity, substantially contributing to ecosystem monitoring and management of MPAs (Cappo et al2003;Jessop et al2022).…”
Section: Introductionmentioning
confidence: 99%